P. 1
PDE Solutions Ch 2-5 (Evans)

PDE Solutions Ch 2-5 (Evans)

4.33

|Views: 5,092|Likes:
Published by i'm not telling

More info:

Published by: i'm not telling on Apr 26, 2013
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

01/09/2015

pdf

text

original

Authors: Joe Benson, Denis Bashkirov, Minsu Kim, Helen Li, Alex Csar

Evans PDE Solutions, Chapter 2
Joe: 1, 2,11; Denis: 4, 6, 14, 18; Minsu: 2,3, 15; Helen: 5,8,13,17. Alex:10, 16
Problem 1. Write down an explicit formula for a function u solving the initial-value problem
_
u
t
+ b · Du + cu = 0 on R
n
× (0, ∞)
u = g on R
n
× {t = 0}
Here c ∈ R and b ∈ R
n
are constants.
Sol: Fix x and t, and consider z(s) := u(x + bs, t + s)
Then
˙ z(s) = b · Du + u
t
= −cu(x + bs, t + s)
= −cz(s)
Therefore, z(s) = De
−cs
, for some constant D. We can solve for D by letting s = −t. Then,
z(−t) = u(x − bt, 0)
= g(x − bt)
= De
ct
i.e. D = g(x − bt)e
−ct
Thus, u(x + bs, t + s) = g(x − bt)e
−c(t+s)
and so when s = 0, we get u(x, t) = g(x − bt)e
−ct
.
Problem 2. Prove that Laplace’s equation ∆u = 0 is rotation invariant; that is, if O is an orthogonal
n × n matrix and we define
v(x) := u(Ox) (x ∈ R)
then ∆v = 0.
Solution:
Let y := Ox, and write O = (a
i j
). Thus,
v(x) = u(Ox)
= u(y)
where y
j
=
_
n
i=1
a
ji
x
i
. This then gives that
∂v
∂x
i
=
n

j=1
∂u
∂y
j
∂y
j
∂x
i
=
n

j=1
∂u
∂y
j
a
ji
1
2
Thus,
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
∂v
∂x
1
.
.
.
∂v
∂x
n
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
=
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
a
11
. . . a
n1
.
.
.
.
.
.
a
1n
. . . a
nn
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
∂u
∂y
1
.
.
.
∂u
∂y
n
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
= O
T
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
∂u
∂y
1
.
.
.
∂u
∂y
n
_
¸
¸
¸
¸
¸
¸
¸
¸
¸
¸
_
D
x
· v = O
T
D
y
· u
Now,
∆v = D
x
v · D
x
v
= (O
T
D
y
u) · (O
T
D
y
u)
= (O
T
D
y
u)
T
O
T
D
y
u
= (D
y
u)
T
(O
T
)
T
O
T
D
y
u
= (D
y
u)
T
OO
T
D
y
u
= (D
y
u)
T
D
y
u because O is orthogonal
= (D
y
u) · (D
y
u)
= ∆u(y)
= 0
Problem 3. Modify the proof of the mean value formulas to show for n ≥ 3 that
u(0) =
1
nα(n)r
n−1
_
∂B(0,r)
gdS +
1
n(n − 2)α(n)
_
B(0,r)
_
1
|x|
n−2

1
r
n−2
_
f dx,
provided
_
¸
¸
_
¸
¸
_
−∆u = f in B
0
(0, r)
u = g on ∂B(0, r).
Solution: Set
φ(t) =
1
nα(n)t
n−1
_
∂B(0,t)
u(y)dS (y), 0 ≤ t < r,
and
φ(r) =
1
nα(n)r
n−1
_
∂B(0,r)
u(y)dS (y) =
1
nα(n)r
n−1
_
∂B(0,r)
gdS.
Then,
φ(t) =
t
n
_
1
α(n)t
n
_
B(0,t)
∆u(y)dy
_
=
t
n
_
1
α(n)t
n
_
B(0,t)
−f dy
_
=
−1
α(n)t
n−1
_
B(0,t)
f dy.
(See the proof of Thm2)
3
Let > 0 be given.
(1) φ() = φ(r) −
_
r

φ(t)dt =
1
nα(n)r
n−1
_
∂B(0,r)
gdS −
_
r

φ(t)dt.
Using integration by parts, we compute

_
r

φ(t)dt =
_
r

1
nα(n)t
n−1
_
B(0,t)
f dydt
=
1
nα(n)
_
r

1
t
n−1
_
B(0,t)
f dydt
=
1
nα(n)
_
_
1
2 − n
1
t
n−2
_
B(0,t)
f dy
_
r


_
r

1
2 − n
1
t
n−2
_
∂B(0,t)
f dS dt
_
=
1
n(n − 2)α(n)
_
_
r

1
t
n−2
_
∂B(0,t)
f dS dt −
1
r
n−2
_
B(0,r)
f dy +
1

n−2
_
B(0,)
f dy
_
=:
1
n(n − 2)α(n)
_
I −
1
r
n−2
_
B(0,r)
f dy + J
_
.
Observe that
J :
1

n−2
_
B(0,)
f dy ≤ C ·
2
, for some constant C > 0
and
_
B(0,)
1
|x|
n−2
f (x)dx =
_
r
0
dt
_
∂B(0,t)
1
t
n−2
f dS.
As → 0, I + J →
_
B(0,)
1
|x|
n−2
f (x)dx. Thus,
lim
→0

_
r

φ(t)dt =
1
n(n − 2)α(n)
_
_
B(0,r)
1
|x|
n−2
f (x)dx −
1
r
n−2
_
B(0,r)
f dy
_
=
1
n(n − 2)α(n)
_
B(0,r)
_
1
|x|
n−2

1
r
n−2
_
f dx.
Therefore, letting → 0, we have from (1)
u(0) = φ(0) =
1
nα(n)r
n−1
_
∂B(0,r)
gdS +
1
n(n − 2)α(n)
_
B(0,r)
_
1
|x|
n−2

1
r
n−2
_
f dx.

Problem 4. We say v ∈ C
2
(
¯
U) is subharmonic if
−∆v ≤ 0 in U.
(a) Prove for subharmonic v that
v(x) ≤

B(x,r)
v dy for all B(x, r) ⊂ U.
(b) Prove that therefore max ¯
U
v = max
∂U
v.
(c) Let φ : R → R be smooth and convex. Assume u is harmonic and v := φ(u). Prove v is
subharmonic.
4
(d) Prove v := |Du|
2
is subharmonic, whenever u is harmonic.
Solution.
(a) As in the proof of Theorem 2, set φ(r) :=

∂B(x,r)
v dS (y) and obtain
φ

(r) =
r
n

B(x,r)
∆v(y)dy ≥ 0.
For 0 < < r,
_
r

φ

(s)ds = φ(r) − φ() ≥ 0.
Hence, φ(r) ≥ lim
→0
φ() = v(x). Therefore,

B(x,r)
v dy =
1
α(n)r
n
_
B(x,r)
v dy =
1
α(n)r
n
_
r
0
__
∂B(x,s)
v(z) dS (z)
_
ds
=
1
α(n)r
n
_
r
0
nα(n)s
n−1
φ(s) ds ≥
1
r
n
_
r
0
ns
n−1
v(x) ds = v(x)
(b) We assume that U ⊂ R
n
is open and bounded. For a moment, we assume also that U is
connected. Suppose that x
0
∈ U is such a point that v(x
0
) = M := max ¯
U
v. Then for
0 < r < dist(x
0
, ∂U),
M = v(x
0
) ≤

B(x
0
,r)
v dy ≤ M.
Due to continuity of v, an equality holds only if v ≡ M within B(x
0
, r). Therefore, the set
u
−1
({M}) ∩ U = {x ∈ U|u(x) = M} is both open and relatively closed in U. By the connect-
edness of U, v is constant within the set U. Hence, it is constant within
¯
U and we conclude
that max ¯
U
v = max
∂U
v.
Now let {U
i
|i ∈ I} be the connected components of U. Pick any x ∈ U and find j ∈ I
such that x ∈ U
j
. We obtain
v(x) ≤ max
¯
U
j
v = max
∂U
j
v ≤ max
∂U
v
and conclude that max ¯
U
v = max
∂U
v.
(c) For x = (x
1
, ..., x
n
) ∈ U and 1 ≤ i, j ≤ n,

2
v
∂x
i
∂x
j
(x) =

2
∂x
i
∂x
j
φ(u(x)) = φ

(u(x)) ·
∂u
∂x
i
(x) ·
∂u
∂x
j
(x) + φ

(u(x)) ·

2
u
∂x
i
∂x
j
(x).
Since φ is convex, then φ

(x) ≥ 0 for any x ∈ R. Recall that u is harmonic and obtain
∆v = φ

(u) ·
n

i=1
_
∂u
∂x
i
_
2
+ ∆u = φ

(u) ·
n

i=1
_
∂u
∂x
i
_
2
≥ 0.
(d) We set v := |Du|
2
=
n
_
k=1
_
∂u
∂x
k
_
2
. For x = (x
1
, ..., x
n
) ∈ U and 1 ≤ i, j ≤ n,

2
v
∂x
i
∂x
j
(x) = 2
n

k=1
_

2
u
∂x
i
∂x
k
(x) ·

2
u
∂x
i
∂x
j
(x) +
∂u
∂x
k
(x) ·

3
u
∂x
i
∂x
j
∂x
k
(x)
_
.
5
Therefore,

2
v
∂x
i
2
= 2
n

k=1
_
¸
¸
¸
¸
¸
_
_

2
u
∂x
i
∂x
k
_
2
+
∂u
∂x
k
·

∂x
k
_

2
u
∂x
i
2
_
_
¸
¸
¸
¸
¸
_
,
∆v = 2

1≤i,k≤n
_

2
u
∂x
i
∂x
k
_
2
+
n

k=1
∂u
∂x
k
·

∂x
k
_
∆u
_
= 2

1≤i,k≤n
_

2
u
∂x
i
∂x
k
_
2
≥ 0.

Problem 5: Prove that there exists a constant C, depending only on n, such that
max
B(0,1)
|u| ≤ C
_
max
∂B(0,1)
|g| + max
B(0,1)
| f |
_
whenever u is a smooth solution of
_
¸
¸
_
¸
¸
_
− u = f in B
0
(0, 1)
u = g on ∂B(0, 1).
Proof: Let M := max
B(0,1)
| f |, then we define v(x) = u(x) +
M
2n
|x|
2
and w(x) = −u(x) +
M
2n
|x|
2
. We
first consider v(x) . Note that
− v = − u − M = f − M ≤ 0.
So, v(x) is a subharmonic funcion.
From Problem 4 (b), we have
max
B(0,1)
v(x) = max
∂B(0,1)
v(x) ≤ max
∂B(0,1)
|g| +
M
2n
.
That is
max
B(0,1)
u(x) ≤ max
B(0,1)
v(x) ≤ max
∂B(0,1)
|g| +
1
2n
max
B(0,1)
| f |.
Then, for w(x), we have
− w = u − M = −f − M ≤ 0.
Again, we can get
max
B(0,1)
w(x) = max
∂B(0,1)
w(x) ≤ max
∂B(0,1)
|g| +
M
2n
.
i.e.
max
B(0,1)
−u(x) ≤ max
B(0,1)
w(x) ≤ max
∂B(0,1)
|g| +
1
2n
max
B(0,1)
| f |.
Combining these two together, we finally proved the problem.
Problem 6. Use Poisson’s formula for the ball to prove
r
n−2
r − |x|
(r + |x|)
n−1
u(0) ≤ u(x) ≤ r
n−2
r + |x|
(r − |x|)
n−1
u(0)
whenever u is positive and harmonic in B
0
(0, r). This is an explicit form of Harnack’s inequality.
6
Solution.
Since y ∈ ∂B(0, r), then |x − y| ≤ |x| + r. Therefore,
u(x) =
r
2
− |x|
2
nα(n)r
_
∂B(0,r)
g(y)
|x − y|
n
dS (y)

r
2
− |x|
2
nα(n)r
_
∂B(0,r)
g(y)
(r + |x|)
n
dS (y) = r
n−2
r − |x|
(r + |x|)
n−1
·
1
nα(n)r
n−1
_
∂B(0,r)
g(y)dS (y)
= r
n−2
r − |x|
(r + |x|)
n−1

∂B(0,r)
g(y)dS (y) = r
n−2
r − |x|
(r + |x|)
n−1
u(0)
The inequality u(x) ≤ r
n−2
r+|x|
(r−|x|)
n−1
u(0) can be proven in a similar way.
Problem 7. Prove Poisson’s formula for a ball: Assume g ∈ C(∂B(0, r)) and let
u(x) =
r
2
− x
2
nα(n)r
_
∂B(0,r)
g(y)
|x − y|
n
dS (y) for x ∈ B
0
(0, r).
Show that
Proof.
Problem 8.
Let u be the solution of
_
¸
¸
_
¸
¸
_
u = 0 in R
n
+
u = g on ∂R
n
+
given by Poisson’s formula for the half-space. Assume g is bounded and g(x) = |x| for x ∈ ∂R
n
+
,
|x| le1. Show Du is not bounded near x = 0. (Hint: Estimate
u(λe
n
)−u(0)
λ
.)
Proof: From formula (33) on page 37, we have
u(x) =
2x
n
nα(n)
_
∂R
n
+
g(y)
|x − y|
n
dy,
and u(0) = g(0) = 0. Thus, using hint, we get
u(λe
n
) − u(0)
λ
=
2
nα(n)
_
∂R
n
+
g(y)
|λe
n
− y|
n
dy
=
2
nα(n)
_
|y|≤1
_
∂R
n
+
g(y)
|λe
n
− y|
n
dy +
2
nα(n)
_
|y|>1
_
∂R
n
+
g(y)
|λe
n
− y|
n
dy
Taking absolute value on both sides, we have
¸
¸
¸
u(λe
n
) − u(0)
λ
¸
¸
¸ ≥
¸
¸
¸
2
nα(n)
_
|y|≤1
_
∂R
n
+
g(y)
|λe
n
− y|
n
dy
¸
¸
¸ −
2
nα(n)
_
|y|>1
_
∂R
n
+
|g(y)|
|λe
n
− y|
n
dy
=I
1
− I
2
.
7
Since g is bounded, so it is obvious that I
2
is bounded and independent of λ. For I
1
, in this case,
g(y) = |y|, so
I
1
=
2
nα(n)
_
|y|≤1
_
∂R
n
+
|y|
|λe
n
− y|
n
dy

2
nα(n)
_
|y|≤1
_
∂R
n
+
|y|
(λ + |y|)
n
dy
Note that for fixed y,
|y|
(λ+|y|)
n
is increasing when λ is decreasing to 0, so by Monotone Convergence
theorem, we have
lim
λ→0
2
nα(n)
_
|y|≤1
_
∂R
n
+
|y|
(λ + |y|)
n
dy
=
_
|y|≤1
_
∂R
n
+
|y|
|y|
n
dy
=
_
B
n−1
(0,1)
|y|
|y|
n
dy
=
_
1
0
dr
_
∂B
n−1
(0,r)
1
|y|
n−1
dS (y) = C
_
1
0
1
r
n−1
r
n−2
dr = ∞.
So, Du is unbounded near x = 0.
Problem 10.
Suppose u is smootha nd solves u
t
− ∆u = 0 in R
n
× (0, ∞).
(i) Show u
λ
(x, t) := u(λx, λ
2
t) also solves the heat equation for each λ ∈ R.
(ii) Use (i) to show v(x, t) := x · Du(x, t) + 2tu
t
(x, t) solves the heat equation as well.
(i) u
λt
(x, t) = λ
2
u
t
(λx, λ
2
t) and u
λx
i
(x, t) = λu(λx, λ
2
t) for each i. Then u
λx
i
x
i
(x, t) = λ
2
u
x
i
(λx, λ
2
t).
Consequently, ∆u
λ
= λ
2
∆u and u
λt
− ∆u
λ
= λ
2
(u
t
− ∆u), so u
λ
solves the heat equation for
all λ ∈ R.
(ii) We differentiate u(λx, λ
2
t) = u(λx
1
, . . . , λx
n
, λ
2
t) with respect to λ we get

k
x
k
u
x
k
(λx
1
, . . . , λx
k
, λ
2
t) + 2λtu
t
(λx
1
, . . . , λx
n
, λ
2
t) = x · D(λx, λ
2
t) + 2tu
t
(λx, λ
2
t).
Taking λ = 1, we then have that v(x, t) = x · Du(x, t) + 2tu
t
(x, t). u is smooth, so the second
derivatives of u(λx, λ
2
t) are continuous, meaning the mixed partials are equal. Therefore,
v
t
−∆v =

∂t∂λ
u(λx, λ
2
t) −∆

∂λ
u(λx, λ
2
t) =

∂λ∂t
u(λx, λ
2
t) −

∂λ
∆u(λx, λ
2
t) =

∂λ
(u
λt
−∆u
λ
) = 0,
since u
λ
satisfies the heat equation for all λ. Thus v does as well.
Problem 11: Assume n = 1 and u(x, t) = v(
x
2
t
).
a) Show
u
t
= u
xx
if and only if
(2) 4zv”(z) + (2 + z)v

(z) = 0 (z > 0)
8
b) Show that the general solution of (1) is
v(z) = c
_
z
0
e
−s/4
s
−1/2
ds + d
c) Differentiate v(
x
2
t
) with respect to x and select the constant c properly, so as to obtain the funda-
mental solution Φ for n = 1.
Solution:
a) Assume that u
t
= u
xx
. Then
u
t
= −
x
2
t
2
v

_
x
2
t
_
and
u
xx
= 2v

_
x
2
t
_
+ 4x
2
v

_
x
2
t
_
So u
t
= u
xx
implies that

x
2
t
2
v

_
x
2
t
_
= 2v

_
x
2
t
_
+ 4x
2
v

_
x
2
t
_
or
4x
2
t
2
v

_
x
2
t
_
+
_
2
t
+
x
2
t
2
_
v

_
x
2
t
_
= 0
If we let z =
x
2
t
, we get
4z
t
v

(z) +
_
2
t
+
z
t
_
v

(z) = 0
Multiplying this equation by t gives the desired equality.
For the other direction, reverse the steps, and hence our proof is done.
b)
4zv

+ (2 + z)v

= 0
=⇒
v

v

= −
1
2
1
z

1
4
=⇒
(by integrating) log(v

) = −log

z −
z
4
+ c
=⇒
v

= Cz
−1/2
e
−z/4
=⇒
v = C
_
z
0
e
−s/4
s
−1/2
ds + d
9
as is desired.
c)
v(z) = c
_
z
0
e
−s/4
s
−1/2
ds + d
=⇒
v
_
x
2
t
_
= c
_ x
2
t
0
e
−s/4
s
−1/2
ds + d
=⇒
v

_
x
2
t
_
= c
2x
t
e

x
2
4t
_
x
2
t
_
−1/2
or
v

_
x
2
t
_
=
2c

t
e

x
2
4t
Now we want to integrate over R and set the integral equal to 1. Thus we get
1 =
2c

t
_


e

x
2
4t
dx
Letting y =
x

4t
, we get dy = (4t)
−1/2
dx and substituting, we get
1 =
2c

t
_



4te
−y
2
dy
or
1 = 4c
_


e
−y
2
dy
Employing the identity
_


e
−y
2
dy =

π and solving for c, we get
c =
1
4

π
Thus,
Φ(x, t) : = v

_
x
2
t
_
=
2c

t
e

x
2
4t
=
1
2

πt
e
−x
2
4t
is easily shown to solve the equation
Φ
t
= Φ
xx

Problem 12. Write down an explicit formula for a solution of
_
¸
¸
_
¸
¸
_
u
t
− ∆u + cu = f in R
n
x(0, ∞)
u = g on R
n
x{t = 0},
where c∈ R.
10
Solution: Set v(x, t) = u(x, t)e
Ct
. Then, v
t
= u
t
e
Ct
+ Ce
Ct
u and v
x
i
x
i
= u
x
i
x
i
e
Ct
.

v
t
− ∆v = u
t
e
Ct
+ Ce
Ct
u − e
Ct
∆u
= e
Ct
(u
t
− ∆u + Cu)
= e
Ct
f .
So, v is a solution of
_
¸
¸
_
¸
¸
_
v
t
− ∆v = e
Ct
f in R
n
x(0, ∞)
v = g on R
n
x{t = 0},
By (17) (p.51),
v(x, t) =
_
R
n
Φ(x − y, t)g(y)dy +
_
t
0
_
R
n
Φ(x − y, t − s)e
Cs
f (y, s)dyds
where Φ is the fundamental solution of the hear equation. Since v(x, t) = u(x, t)e
Ct
, we have
u(x, t) = e
Ct
_
_
R
n
Φ(x − y, t)g(y)dy +
_
t
0
_
R
n
Φ(x − y, t − s)e
Cs
f (y, s)dyds
_
.

Problem 13: Given g : [0, ∞] → R, with g(0) = 0, derive the formula
u(x, t) =
x


_
t
0
1
(t − s)
3/2
e
−x
2
4(t−s)
g(s)ds, x > 0
for a solution of the initial/boundary-value problem
_
¸
¸
¸
¸
_
¸
¸
¸
¸
_
u
t
− u
xx
= 0 inR
+
× (0, ∞)
u = 0 onR
+
× {t = 0},
u = g on{x = 0} × [0, ∞).
Proof. We define
v(x, t) =
_
¸
¸
_
¸
¸
_
u(x, t) − g(t) x > 0,
−u(−x, t) + g(t) x ≤ 0.
So, we have
v
t
(x, t) =
_
¸
¸
_
¸
¸
_
u
t
(x, t) − g

(t) x > 0,
−u
t
(−x, t) + g

(t) x ≤ 0,
and
v
xx
(x, t) =
_
¸
¸
_
¸
¸
_
u
xx
(x, t) x > 0,
−u
xx
(−x, t) x ≤ 0.
11
Hence,
_
¸
¸
¸
¸
¸
¸
¸
¸
_
¸
¸
¸
¸
¸
¸
¸
¸
_
v
t
(x, t) − v
xx
(x, t) =
_
¸
¸
_
¸
¸
_
−g

(t) x > 0,
g

(t) x ≤ 0.
v(x, 0) = 0,
v(0, t) = 0.
By formula (13) on page 49, we get
v(x, t) =
_
t
0
1

4π(t − s)
__
0
−∞
e
−(y−x)
2
4(t−s)
g

(s)dyds −
_

0
e
−(y−x)
2
4(t−s)
g

(s)dyds
_
Note that(page 46 Lemma)
_

−∞
1

4π(t − s)
e
−(y−x)
2
4(t−s)
dy = 1,
so when x > 0, we let y − x = −z and obtain
u(x, t) = v(x, t) + g(t)
= v(x, t) +
_
t
0
g

(s)ds
_

−∞
1

4π(t − s)
e
−(y−x)
2
4(t−s)
dy
= 2
_
t
0
1


(t − s)

1
2
_
0
−∞
e
−(y−x)
2
4(t−s)
dy g

(s)ds
=
_
t
0
1

π
(t − s)

1
2
_

x
e
−z
2
4(t−s)
dz dg(s)
Integrating by parts, we get
u(x, t) =
1

π
(t − s)
−1/2
_

x
e
−z
2
4(t−s)
dz g(s)|
s=t
s=0

_
t
0
g(s)
1

π
1
2
(t − s)
−3/2
ds
_

x
e
−z
2
4(t−s)
dz

_
t
0
g(s)
1

π
(t − s)
−1/2
ds
_

x
e
−z
2
4(t−s)
−z
2
4(t − s)
2
dz
= I
1

_
t
0
g(s)
1

π
1
2
(t − s)
−3/2
ds
_

x
e
−z
2
4(t−s)
dz
+
_
t
0
g(s)
1

π
(t − s)
−1/2
ds
_

x
−z
2(t − s)
de
−z
2
4(t−s)
= I
1

_
t
0
g(s)
1

π
1
2
(t − s)
−3/2
ds
_

x
e
−z
2
4(t−s)
dz
+
_
t
0
g(s)
1


(t − s)
−3/2
ds (−z) e
−z
2
4(t−s)
|
z=∞
z=x
+
_
t
0
g(s)
1

π
1
2
(t − s)
−3/2
ds
_

x
e
−z
2
4(t−s)
dz
= I
1
+
x


_
t
0
1
(t − s)
3/2
e
−x
2
4(t−s)
g(s)ds.
12
Now, we focus on I
1
and define w
2
to be
z
2
4
,
I
1
= lim
→0
+
1

π

−1/2
_

x
e
−z
2
4
dz g(t − )
= g(t) lim
→0
+
1

π
_

x
2
/4
2e
−w
2
dw = 0.
Thus, we proved
u(x, t) =
x


_
t
0
1
(t − s)
3/2
e
−x
2
4(t−s)
g(s)ds, x > 0.
Next, we need to show that
lim
x→0
+
u(x, t) = g(t).
Note that for any fixed δ > 0.
lim
x→0
+
u(x, t) = lim
x→0
+
x


_
t
t−δ
1
(t − s)
3/2
e
−x
2
4(t−s)
g(s)ds
+ lim
x→0
+
x


_
t−δ
0
1
(t − s)
3/2
e
−x
2
4(t−s)
g(s)ds
= g(t) lim
x→0
+
x


_
t
t−δ
1
(t − s)
3/2
e
−x
2
4(t−s)
ds
= g(t) lim
x→0
+
x


_
δ
0
1
s
3/2
e
−x
2
4s
ds
For fixed x, we let s = x
2
/w
2
and get
lim
x→0
+
u(x, t) = g(t) lim
x→0
+
x
2

π
_
x
2


w
3
x
3
e
−w
2
4
−2x
2
w
3
dw
= g(t) lim
x→0
+
1

π
_

x
2

e
−w
2
4
dw
= g(t)
1

π
_

0
e
−w
2
4
dw = g(t).
Hence, we are done.
Problem 14. We say v ∈ C
2
1
(U
T
) is a subsolution of the heat equation if
v
t
− ∆v ≤ 0 in U
T
.
(a) Prove for a subsolution v that
v(x, t) ≤
1
4r
n
_ _
E(x,t;r)
v(y, s)
|x − y|
2
(t − s)
2
dyds
for all E(x, t; r) ⊂ U
T
.
(b) Prove that therefore max ¯
U
T
v = max
Γ
T
v
13
Solution.
(a) We may well assume upon translating the space and time coordinates that x = 0 and t = 0.
As in the proof of Theorem 3, set
φ(r) :=
1
r
n
_ _
E(r)
v(y, s)
|y|
2
s
2
dyds,
ψ(y, s) := −
n
2
log(−4πs) +
|y|
2
4s
+ n log r
and derive
φ

(r) ≥
1
r
n+1
_ _
E(r)
−4n∆vψ −
2n
s
n

i=1
v
y
i
y
i
dyds
=
n

i=1
1
r
n+1
_ _
E(r)
4nv
y
i
ψ
y
i

2n
s
v
y
i
y
i
dyds = 0.
For 0 < < r,
r
_

φ

(z)dz = φ(r) − φ() ≥ 0.
Hence, φ(r) ≥ lim
→0
φ() = v(0, 0) · lim
→0
1

n
_ _
E()
|y|
2
s
2
dyds = 4v(0, 0), and the statement follows.
(b) Suppose there exists a point (x
0
, t
0
) ∈ U
T
with u(x
0
, t
0
) = M := max ¯
U
T
u. Then for all
sufficiently small r > 0, E(x
0
, t
0
; r) ⊂ U
T
. Using the result proved above, we deduce
M = v(x
0
, t
0
) ≤
1
4r
n
_ _
E(x
0
,t
0
;r)
v(y, s)
|x − y|
2
(t − s)
2
dyds ≤ M,
since
1 =
1
4r
n
_ _
E(x
0
,t
0
;r)
|x
0
− y|
2
(t
0
− s)
2
dyds.
Conclude that u|
E(x
0
,t
0
;r)
= M. The argument used in the proof of Theorem 4 will finish the
proof.

Problem 15.
(a) Show the general solution of the PDE u
xy
= 0 is
u(x, y) = F(x) + G(y)
for arbitrary functions F,G.
(b) Using the change of variables ξ = x + t, η = x − t, show u
tt
− u
xx
= 0 if and only if u
ξη
= 0.
(c) Use (a),(b) to rederive d’Alembert’s formula.
Solution:
(a)
u
xy
= 0 ⇒ u
x
= f (x) ⇒ u(x, y) =
_
f (x)dx + G(y)
u
yx
= 0 ⇒ u
y
= g(y) ⇒ u(x, y) =
_
g(y)dy + F(x)
14
This implies u(x, y) = F(x) + G(y).
(b)
x =
ξ+η
2
, y =
ξ−η
2
Define ˜ u := u
_
ξ+η
2
,
ξ−η
2
_
˜ u
ξ
=
1
2
u
x
+
1
2
u
t
and ˜ u
ξη
=
1
4
u
xx

1
4
u
xt
+
1
4
u
tx

1
4
u
tt
=
1
4
(u
xx
− u
tt
)
Hence, ˜ u
ξη
= 0 ⇔ u
tt
− u
xx
= 0.
(c)
By (b), u
tt
− u
xx
= 0 ⇒ u
ξη
= 0, and u(ξ, η) = F(ξ) + G(η) by (a)
,i.e, u(x, y) = F(x + t) + G(x − t).
Since u(x, 0) = g, u
t
(x, 0) = h,
(3) u(x, 0) = F(x) + G(x) = g(x),
u
t
(x, 0) = F

(x) − G

(x) = h(x)
Integration ⇒
(4) F(x) − G(x) =
_
x
0
h(y)dy + C, C:constant.
(2) + (3); F(x) =
1
2
_
g(x) +
_
x
0
h(y)dy + C
_
(2) − (3); G(x) =
1
2
_
g(x) −
_
x
0
h(y)dy − C
_
Thus,
u(x, y) = F(x + t) + G(x − t) =
1
2
_
g(x + t) +
_
x+t
0
h(y)dy + C
_
+
1
2
_
g(x − t) −
_
x−t
0
h(y)dy − C
_
=
1
2
_
g(x + t) +
_
x+t
0
h(y)dy + C + g(x − t) +
_
0
x−t
h(y)dy − C
_
=
1
2
_
g(x + t) + g(x − t)
_
+
1
2
_
x+t
x−t
h(y)dy (x ∈ R, t ≥ 0).

Problem 16.
Assume E = (E
1
, E
2
, E
3
) and B = (B
1
, B
2
, B
3
) solve Maxwell’s equations:
E
t
= curl B
B
t
= −curl E
div B = div E = 0
Show that u
tt
− ∆u = 0 where u = B
i
or E
i
for i = 1, 2, 3.
Solution.
15
curl(curl E) = curl(−B
t
)
=
_


2
B
3
∂y∂t
+

2
B
2
∂z∂t
, −

2
B
3
∂x∂t
+

2
B
1
∂z∂t
, −

2
B
2
∂x∂t
+
∂B
1
∂y∂t
_
= −

∂t
curl B
= −

∂t
E
t
= −

2
E
∂t
2
However, we also know that curl(curl E) = ∇(div E) − ∇
2
E = −∇
2
E. Then E
i
satisfies u
tt
− ∆u = 0
for i = 1, 2, 3.
Similarly, curl(curl B) = curl E
t
= −

2
B
∂t
2
, and curl(curl B) = ∇(div B) − ∇
2
B = −∇
2
B, so B
i
satisfies
u
tt
− ∆u = 0 for i = 1, 2, 3.
Problem 17.(Equipartition of energy) Let u ∈ C
2
(R × [0, ∞)) solve the initial value problem for
the wave equation in one dimension:
_
¸
¸
_
¸
¸
_
u
tt
− u
xx
= 0 in R × (0, ∞)
u = g; u
t
= h on R × {t = 0}.
Suppose g, h have compact support. The kinetic energy is k(t) :=
1
2
_

−∞
u
2
t
(x, t)dx and the potential
energy is p(t) :=
1
2
_

−∞
u
2
x
(x, t)dx. Prove
(i) k(t) + p(t) is constant in t.
(ii) k(t) = p(t) for all large enough times t.
Proof. (i.) We define e(t) = k(t) + p(t) =
1
2
_

−∞
_
u
2
t
+ u
2
x
_
dx. Since g, h have compact support, so
we have
d e(t)
dt
=
1
2
_

−∞
2u
t
u
tt
+ 2u
x
u
xt
dx
_

−∞
u
t
u
tt
dx −
_

−∞
u
xx
u
t
dx
=
_

−∞
u
t
(u
tt
− u
xx
) dx = 0.
Hence, e(t) ≡ e(0).
(ii.)By d’Alembert’s formula on page 68, we have
u(x, t) =
1
2
_
g(x + t) + g(x − t)
_
+
1
2
_
x+t
x−t
h(y)dy.
So,
u
t
=
1
2
_
g

(x + t) − g

(x − t)
_
+
1
2
[h(x + t) + h(x − t)] ,
and
u
x
=
1
2
_
g

(x + t) + g

(x − t)
_
+
1
2
[h(x + t) − h(x − t)] .
16
We assume that there exists a positive constant M so that [−M, M] ⊇ supp(g

) and [−M, M] ⊇
supp(h).
Note that for a fixed t > M, −M ≤ x − t ≤ M ⇔ 0 < t − M ≤ x ≤ t + M and −M ≤ x + t ≤ M ⇔
−t − M ≤ x ≤ −t + M < 0.
Thus, when t > M :
(a) 0 < t − M ≤ x ≤ t + M.
Then we have
h(x + t) = g(x + t) = 0.
So,
u
2
t
=
1
4
g

(x − t)
2
+
1
4
h(x − t)
2

1
2
g

(x − t)h(x − t) = u
2
x
.
(b) −t − M ≤ x ≤ −t + M < 0.
Then,
u
2
t
=
1
4
g

(x + t)
2
+
1
4
h(x + t)
2
+
1
2
g

(x + t)h(x + t) = u
2
x
.
(c) Otherwise
g

(x + t) = g

(x − t) = h(x + t) = h(x − t) = 0.
So, combining all the cases, it is obvious that when t > M, k(t) = p(t).
Problem 18. Let u solve
_
u
tt
− ∆u = 0 in R
3
× (0, ∞)
u = g, u
t
= h on R
3
× {t = 0},
where g, h are smooth and have compact support. Show there exists a constant C such that
|u(x, t)| ≤ C/t (x ∈ R
3
, t > 0).
Solution.
From the conditions it follows that there exist R, M > 0 such that spt g, spt h ⊂ B(0, R) and
g(y) ≤ M, |Dg(y)| ≤ M, h(y) ≤ M for any y ∈ R
3
. Kirchhoff’s formula gives the solution of the
initial-value problem:
u(x, t) =

∂B(x,t)
th(y) + g(y) + Dg(y) · (y − x) dS (y).
Denote by Σ the intersection ∂B(x, t) ∩ B(0, R). Observe that the area of Σ is not greater than the
area of the sphere ∂B(0, R). Then, for t > 0, we obtain
¸
¸
¸
¸
¸
¸

∂B(x,t)
th(y) + Dg(y) · (y − x) dS (y)
¸
¸
¸
¸
¸
¸
=
1
4πt
2
¸
¸
¸
¸
¸
¸
_
∂B(x,t)∩B(0,R)
th(y) + Dg(y) · (y − x) dS (y)
¸
¸
¸
¸
¸
¸

1
4πt
2
_
∂B(x,t)∩B(0,R)
t · |h(y)| + |Dg(y)| · |y − x| dS (y)

1
4πt
2
· 4πR
2
· (tM + tM) =
2R
2
M
t
.
17
For t > 1, using the same argument, we get
¸
¸
¸
¸
¸
¸

∂B(x,t)
g(y) dS (y)
¸
¸
¸
¸
¸
¸
=
1
4πt
2
¸
¸
¸
¸
¸
¸
_
∂B(x,t)∩B(0,R)
g(y) dS (y)
¸
¸
¸
¸
¸
¸

1
4πt
2
· 4πR
2
· M =
R
2
M
t
2

R
2
M
t
.
Notice now that the area Σ is not greater than the area of the sphere ∂B(x, t). Then for 0 < t ≤ 1,
¸
¸
¸
¸
¸
¸

∂B(x,t)
g(y) dS (y)
¸
¸
¸
¸
¸
¸
=
1
4πt
2
¸
¸
¸
¸
¸
¸
_
∂B(x,t)∩B(0,R)
g(y) dS (y)
¸
¸
¸
¸
¸
¸

1
4πt
2
· 4πt
2
· M ≤
M
t
.
Without loss of generality, we can take R > 1. Then, combining the estimates obtained above, we
conclude |u(x, t)| ≤
3R
2
M
t
.
Evans PDE Solutions, Chapter 5
Alex: 4, Helen: 5, Rob H.: 1
Problem 1.
Suppose k ∈ {0, 1, . . .}, 0 < γ < 1. Prove C
k,γ
(
¯
U) is a Banach space.
Solution:
1. First we show that || · ||
C
k,γ
(
¯
U)
is a norm, where we recall that
||u||
C
k,γ
(
¯
U)
=

|α|≤k
||D
α
u||
C(
¯
U)
+

|α|=k
[D
α
u]
C
0,γ
(
¯
U)
,
and
[u]
C
0,γ
(
¯
U)
= sup
xy∈U
_
|u(x) − u(y)|
|x − y|
γ
_
.
For the sake of opaqueness we now omit subscripts on all norms unless it is unclear from context.
2. For any λ ∈ R we have first
[λu] = sup
x,y∈U
|λu(x) − λu(y)|
|x − y|
γ
= |λ| sup
x,y∈U
|u(x) − u(y)|
|x − y|
γ
= |λ| [u] ,
and certainly
||D
α
(λu)||
C(
¯
U)
= ||λD
α
u|| = |λ| · ||D
α
u|| .
So
||λu|| =

|α|≤k
||D
α
(λu)|| +

|α|=k
[D
α
(λu)]
= |λ|

|α|≤k
||D
α
u|| + |λ|

|α|=k
[D
α
u]
= |λ| · ||u|| .
3. If u = 0 it is obvious that ||u|| = 0. On the other hand, ||u|| = 0 implies that
||D
α
u||
C(
¯
U)
= 0
18
for every |α| ≤ k. In particular this is true for α = 0 so that the supremum of D
0
u = u on U is 0, i.e.
u ≡ 0.
4. Finally we must prove the triangle inequality. We know the triangle inequality is true for the sup
norm || · ||
C(
¯
U)
. We can also see that for any α which makes sense
[D
α
(u + v)] = [D
α
u + D
α
v] ≤ [D
α
u] + [D
α
v] .
Therefore we can easily conclude
||u + v|| =

|α|≤k
||D
α
(u + v)|| +

|α|=k
[D
α
(u + v)]

|α|≤k
(||D
α
u|| + ||D
α
v||) +

|α|=k
([D
α
u] + [D
α
v])
= ||u|| + ||v||.
5. We need only show that C
k,γ
(U) is complete. So let {u
m
} be a Cauchy sequence. Then {u
m
(x){
is a Cauchy sequence for every x, so define u to be the pointwise limit of the u
m
. Now if V is any
bounded subset of U, then
¯
V is compact, so that u
m
⇒ u uniformly on any V. Since the u
m
are
uniformly continuous on
¯
V by assumption, this implies that u is uniformly continuous on
¯
V as well
(and so, a fortiori u ∈ C(U)). Therefore u ∈ C(
¯
U).
What we would really like would be to have u ∈ C
k
(
¯
U). But similar arguments show that u has
derivatives D
α
u for all |α| ≤ k on U by restricting first to bounded subsets of U to find the derivatives
and then using uniformconvergence on these subsets to showthe derivatives must also be uniformly
continuous on bounded subsets since the D
α
u
m
were.
This leaves us with only showing that the norm of u is finite, so that in fact u ∈ C
k,γ
(U). But for
every n we have
||u
n
− u|| =

|α|≤k
sup
x∈U
|D
α
u
n
(x) − D
α
u(x)| +

|α|=k
sup
x,y∈U
|D
α
u
n
(x) − D
α
u
n
(y) − D
α
u(x) + D
α
u(y)|
|x − y|
γ
= lim
m⇒∞
_
¸
¸
¸
¸
¸
¸
_

|α|≤k
sup
x∈U
|D
α
u
n
(x) − D
α
u
m
(x)| +

|α|=k
sup
x,y∈U
|D
α
u
n
(x) − D
α
u
n
(y) − D
α
u
m
(x) + D
α
u
m
(y)|
|x − y|
γ
_
¸
¸
¸
¸
¸
¸
_
= lim
m⇒∞
||u
n
− u
m
||.
In particular, since {u
m
} is Cauchy there is some N so that n, m ≥ N implies ||u
n
− u
m
|| ≤ 1. Letting
m approach ∞, this implies that ||u
N
− u|| < 1. Now the triangle inequality applies to give
||u|| ≤ ||u
N
− u|| + ||u
N
|| < 1 + ||u
N
|| < ∞.

Problem 4.
Assume U is bounded and U ⊂⊂
_
N
i=1
V
i
. Show there exist C

functions ζ
i
(i = 1, . . . , N) such that
_
¸
¸
_
¸
¸
_
0 ≤ ζ
1
≤ 1, supp ζ
i
⊂ V
i
i = 1, . . . , N
_
N
i=1
ζ
i
= 1 on U.
The functions {ζ
i
}
N
1
for a partition of unity.
19
Solution. Assume U is bounded and U ⊂⊂
_
N
i=1
V
i
. Without loss of generality, we may assume
that the V
i
are open, for if they are not, we can replace V
i
by its interior. We note that, since U is
bounded, U is compact. Each x ∈ U has a compact neighbourhood N
x
contained in V
i
for some i.
Then {N

x
} is an open cover of U, which then has a finite subcover N

x
1
, . . . , N

x
n
. We now let F
i
be
the union of the N
x
k
contained in V
i
. F
i
is the compact since it is the finite union of compact sets.
The C

version of Urysohn’s Lemma (Folland, p.245) allows us to find smooth functions ξ
1
, . . . , ξ
N
such that ξ
i
= 1 on F
i
and supp(ξ
i
) ⊂ V
i
. Since the F
i
cover U, U ⊂ {x :
_
n
1
ξ
i
(x) > 0} and we can
use Urysohn again to find ζ ∈ C

with ζ = 1 on U and supp(ζ) ⊂ {x :
_
n
1
ξ
i
(x) > 0}. Now, we let
ξ
N
1
= 1 − ζ, so
_
N+1
1
ξ
i
> 0 everywhere. We then take
ζ
i
=
ξ
i
_
N+1
1
ξ
j
as our partition of unity.
Problem 5 (Helen) Prove that if n = 1 and u ∈ W
1, p
(0, 1) for some 1 ≤ p < ∞, then u is equal a.e.
to an absolutely continuous function, and u

which exists a.e. belongs to L
p
(0, 1).
Proof. Since u ∈ W
1,p
(0, 1), so by definition on page 242 and 244, we have some function v ∈
L
p
(0, 1) such that
_
(0,1)
u Dφdx = −
_
(0,1)
vφdx, ∀φ ∈ C

c
((0, 1)) .
Note that v ∈ L
p
(0, 1), so by H¨ older’s inequality, we have v
L
1 ≤ v
L
p 1
L
q < ∞, which means
v ∈ L
1
(0, 1). Thus, we can define function f (x) on (0, 1) by the following formula
f (x) = u(
1
2
) +
_
x
1
2
v(t)dt, ∀x ∈ (0, 1).
According to the Fundamental Theorem of Calcalus, f is absolutely continuous. Now we will
prove u = f a.e.
By the definition of f , we have f

= v a.e. So for any φ ∈ C

c
((0, 1)) we get
_
(0,1)
f Dφdx = −
_
(0,1)
f

φdx = −
_
(0,1)
vφdx.
Therefore,
_
(0,1)
( f − u) Dφdx = 0 ∀φ ∈ C

c
((0, 1)) ,
which means u = f + const. And note that u(
1
2
) = f (
1
2
), hence u = f a.e. So u

exists a.e. and
satisfy u

= v a.e., so u

∈ L
p
(0, 1).

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->